Study on Preservation of Chilled Beef with Natural Essential Oil Nanocapsules - Bin Xi; Yaqin Gao; Tianfen Guo; Weihong Li; Xiaoling Yang; Tianqing Du (Journal of Chemistry)
Beef is rich in amino acids and vitamin B6, carnitine, potassium, protein, and other nutrients. It can improve the body’s ability to resist disease and is especially suitable for growth, development, and postoperation and postrehabilitation care. Under such circumstances, the demand for beef consumption in various countries continues to grow steadily. At present, domestic beef prices continue to rise, and beef supply is insufficient. In addition, fresh beef is easy to be infected with microorganisms in the process of cold storage, which makes fresh beef deteriorated. Therefore, it is very important to add preservatives to prolong the shelf life of chilled beef. In this paper, the preservation of chilled beef with nanocapsules made of natural essential oil from plant extracts was studied. In this study, cumin, Zanthoxylum, ginger, cinnamon, clove, and thyme were selected to study the effect of six kinds of essential oils on beef preservation through comparative experiments. On the basis of such research data, the six kinds of essential oils were compounded, respectively, and different nanoessential oil capsules were applied to the fresh-keeping of chilled beef to make different kinds of nanoessential oil capsules. Through the experiment, the compound essential oil with better preservation effect was obtained. And through the comparison, cinnamon essential oil has obvious antibacterial activity, while ginger essential oil has the worst antibacterial effect. The pH value of beef can be changed and the degradation rate of protein in beef will be slowed down by applying appropriate amount of decomposed plant essential oil to beef samples. Through the above experimental results, we applied the compound essential oil to the preservation of cold and fresh beef at nanometer level and found that the effect was significant, which was worthy of application in major beef products processing plants.